2021
DOI: 10.3390/w13213030
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD Purification and Characterization of Meta-Cresol-Purple for Spectrophotometric Seawater pH Measurements

Abstract: High-quality pH measurements are essential for observing ocean acidification and interpreting its chemical and ecological effects. Spectrophotometric measure is the preferred method for pH analysis of seawater because of its high reproducibility and excellent precision. Meta-cresol purple (mCP) is one of the most used indicator dyes for spectrophotometric pH determination. Impurities in indicator salts can significantly bias spectrophotometric pH determinations, and therefore the use of purified mCP is recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They further showed that the differences could be attributed to impurities in the indicator dye solutions that result in lower measured pH T . Liu et al (2011) and Rivaro et al (2021) used high performance liquid chromatography (HPLC) and Patsavas et al (2013) used flash chromatography to purify indicator dyes from a variety of manufacturers and showed that a single research group could purify indicator dyes from multiple sources and produce a consistent product. More recently, Takeshita et al (2021) organized an inter‐laboratory comparison of purified mCP indicator dyes and found that seven of nine batches of purified indicator dye obtained from four suppliers across two countries produced pH T measurements that agreed within 0.003 across pH T values, while two of nine batches produced quantifiably different pH T values (attributed to remaining impurities).…”
Section: Uncertainty Sources By Measurable Variablementioning
confidence: 99%
“…They further showed that the differences could be attributed to impurities in the indicator dye solutions that result in lower measured pH T . Liu et al (2011) and Rivaro et al (2021) used high performance liquid chromatography (HPLC) and Patsavas et al (2013) used flash chromatography to purify indicator dyes from a variety of manufacturers and showed that a single research group could purify indicator dyes from multiple sources and produce a consistent product. More recently, Takeshita et al (2021) organized an inter‐laboratory comparison of purified mCP indicator dyes and found that seven of nine batches of purified indicator dye obtained from four suppliers across two countries produced pH T measurements that agreed within 0.003 across pH T values, while two of nine batches produced quantifiably different pH T values (attributed to remaining impurities).…”
Section: Uncertainty Sources By Measurable Variablementioning
confidence: 99%